COMPARISON OF THE EFFICACY OF ATOMIZED VERSUS NEBULIZED LOCAL ANESTHETIC FOR AWAKE NASAL FIBEROPTIC INTUBATION: A RANDOMIZED TRIAL. - Nanda, Kasturi; Sinha, Aparajita; Agarwal, Anshika (Student's Journal of Health Research Africa, 2024)
Background Awake fiberoptic intubation (AFOI) is a critical technique for managing difficult airways requiring effective local anesthesia to ensure patient comfort and procedural success. Nebulization and atomization have been employed for the topicalization of the airway. This study compared the efficacy of atomized versus nebulized local anesthesia for awake fiberoptic intubations. Methods A random assignment was made to provide either atomized (n = 35) or nebulized (n = 35) local anesthetic to seventy adult patients who needed AFOI. Time to intubation and attempts for intubation were the primary outcomes while patient satisfaction, adverse hemodynamic changes, and complications were secondary outcomes. With p < 0.05 designated as the statistical significance level, the data were analyzed using SPSS version 21.0. Results: The atomized group had a shorter intubation time (4.9 ± 1.1 vs. 7.0 ± 1.5 minutes, p < 0.001) and higher first-attempt success (85.7% vs. 62.9%, p = 0.005). Fewer required a second attempt (14.3% vs. 37.1%). The atomized group also had smaller increases in MAP (10.2 ± 2.1 vs. 12.5 ± 2.3 mmHg, p = 0.03) and HR (9.5 ± 1.9 vs. 12.3 ± 2.1 bpm, p = 0.01). Patient satisfaction was higher (9.0 ± 1.0 vs. 7.4 ± 1.3, p = 0.002), and complications like coughing, gagging, and desaturation were fewer but not statistically significant. Conclusion Atomized local anesthesia proved more effective than nebulized anesthesia for awake fiberoptic intubation, offering higher patient comfort, easier and quicker intubation, and greater satisfaction. Although complications were fewer with atomization, further research is needed. Thus, atomized anesthesia is recommended as the preferred method for AFOI. Recommendations Atomized local anesthesia is recommended for AFOI, particularly in patients with difficult airways, due to its higher efficacy and patient satisfaction. To validate these results and investigate long-term consequences, further extensive research is required.